Multiply: (5xy^4)(2x^2y)

Question

Asked 2/9/2013 1:05:19 PM

Updated 2/28/2018 11:30:36 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [2/28/2018 11:30:36 AM]

s

michelledayag|Points 59|

Question

Asked 2/9/2013 1:05:19 PM

Updated 2/28/2018 11:30:36 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [2/28/2018 11:30:36 AM]

Rating

3

(5xy^4)(2x^2y) = 10x^3y^5

Added 2/28/2018 11:30:35 AM

This answer has been confirmed as correct and helpful.

Simplify: 2x+6+5x-3 **Weegy:** 2x+6+5x-3 = 7x +3 (More)

Question

Updated 3/26/2014 6:42:40 AM

1 Answer/Comment

samn

M

2x+6+5x-3

2x+5x+6-3

7x+3

2x+5x+6-3

7x+3

Added 2/21/2013 5:25:27 AM

This answer has been flagged as incorrect.

Flagged by andrewpallarca [3/26/2014 6:42:30 AM]

Solve for x : -2(x - 4) = -3(x + 8) **Weegy:** +3+2=5 (More)

Question

Updated 2/9/2013 3:30:25 PM

1 Answer/Comment

-2(x - 4) = -3(x + 8)

-2x + 8 = -3x - 24

-2x + 3x = -24 - 8

x = -32

-2x + 8 = -3x - 24

-2x + 3x = -24 - 8

x = -32

Added 2/9/2013 3:30:25 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/26/2014 6:41:59 AM]

Solve for x: -3x + 2 = 35 **Weegy:** X stands for the number that -3 will be multiplyed by to get 6. As we both should know, to get a positive number out a negative, you have to multiply TWO negatives together to get a positive. so what will give you 6 when multiplyed by 3? -3(x)= 6. [ we know that 3 times 2 will give us 6. So, in order to make a positive six we will multiply -3(-2) which will give us 6. ] (More)

Question

Updated 2/9/2013 3:29:01 PM

1 Answer/Comment

-3x + 2 = 35

-3x = 35 - 2

-3x = 33

x = 33 / -3

x = -11

-3x = 35 - 2

-3x = 33

x = 33 / -3

x = -11

Added 2/9/2013 3:29:01 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/26/2014 6:43:16 AM]

(5x^2+6x+4)+(7x^2+2x-4) **Weegy:** 8x - 2x^2 is the answer. (5x^2+6x+4)+(-7x^2+2x-4) = 8x - 2x^2 **User:** True or false: x^0 is equal to 1 (More)

Question

Updated 3/26/2014 6:43:09 AM

2 Answers/Comments

(5x^2+6x+4)+(7x^2+2x-4)

= 12x^2 + 8x

= 12x^2 + 8x

Added 2/9/2013 2:49:33 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/26/2014 6:42:58 AM]

x^0 is equal to 1. This is TRUE.

Added 2/9/2013 2:49:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/26/2014 6:43:10 AM]

32,269,645

questions answered

There are no comments.